Pengaruh Desain Cerobong Boiler Terhadap Sebaran Emisi Partikulat Menggunakan Perangkat Pemodelan Aermod - Prabasari, Ira; Hutagalung, Winny Laura Christina; Bahar, Fetty Febriasti; Kumalasari, Dyah (Jurnal Teknik, 2025)
Particulate emissions from boiler activities are known has a negative impact on health, such as causing respiratory problems. The particulate emission dispersion model generated from the chimney of a boiler can be known using the aermod modeling tool, through this model, the concentration of particulate emissions received by the environment around the activity can be studied. The design of the boiler chimney is also known to affect the concentration of particulate matter that is dispersed. This study aims to determine the effect of chimney design on the distribution of particulate emissions from boilers activities. The particulate dispersion model was carried out using the aermod modeling tool with several fixed variables, namely climatic conditions, the location of chimney and reseptor, and particulate emissions coming out from boiler, while the independent variables were variations in chimney diameter and heights. The results of particulate distribution model show that chimneys with a diameter of 2 meters and a height of 28 meters have a wider distribution of 93.96 meters from the emission source with a maximum concentration of 29.41 µm/Nm3. While the lowest concentration received by the receptor of 2.51 µm/Nm3 came from the chimney with a larger diameter and higher chimney.